For x = -3, <span>(-0.7x) equals (-0.7[-3]), or 2.1.
8 8 8
Then f(-3) = ------------------- = ---------------- = ------------ = 0.31 (approx)
1 + 3*e^2.1 1 + 24.499 25.5</span>
Answer:
use The Explicit Formula for the Fibonacci Sequence
Step-by-step explanation:
This is not true. The infinite series

converges if and only if the sequence of its partial sums converges. The

-th partial sum is

but clearly this diverges as

gets arbitrarily large.
Answer: 0.000
Step-by-step explanation:
The exponent of a number says how many times to use the number in a multiplication.
For Example, In 8² , the 2 is the number of times 8 has to be multiplied. In this case It has to multiplied by itself 2 times, 8x8 = 64 so 8² = 64.
Another example is 9³ since the number above is 3 we have to multiply 9 three times, 9x9x9 = 729 which means 9³ = 729.
Hope this helps